(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Corporate governance and financial risk have been extensively researched, especially after the 2008 global financial crisis. The emergence of corporate governance as a key area of focus in various fields of research such as management, economics, law, and business is due to corporate failures and scandals. Hence, this paper seeks to investigate whether corporate mechanisms have a significant impact on non-financial companies, particularly those listed on Omani’s Muscat Securities Market. Design/methodology/approach: This study uses characteristics of corporate governance to investigate the financial risk activities of 116 companies listed on the Muscat Securities Market. The characteristics to be used as the independent variables (IV) are the companies’ board composition and size, ownership concentration, regulatory compliance, executive compensation, and information disclosure. The IVs will be used to examine whether corporate governance directly affects the dependent variables financial and investors’ perspective risks when moderated by the firm’s profitability, size, and risk management control. To test these variables, Generalized Method of Moments (GMM) for data analysis will be used, as it allows equitable and reliable approximations whilst establishing corporate governance’s link between financial risk. Findings: Findings from this study are hoped to fill the knowledge gap on corporate governance and financial risks among non-financial institutions in the Omani context. Practical Implications: Finance and making investment-related decisions while managing risk are strongly correlated. It is believed that the effectiveness of corporate governance processes reduces risk with the purpose of benefiting leadership and ethical codes of conduct.